An Important Clue in the Sonographic Diagnosis of Internal Carotid Artery Agenesis: Ipsilateral Common Carotid Artery Hypoplasia. (1st July 2014) - Kaya, Omer; Yilmaz, Cengiz; Gulek, Bozkurt; Soker, Gokhan; Cikman, Gokalp; Inan, Ibrahim; Demirduzen, Selahaddin
Abstract : A 42-year-old female patient, who had been diagnosed with an occlusion of her left internal carotid artery (ICA) following Doppler ultrasonographic (US) and digitally-subtracted angiographic (DSA) examinations performed in an outer healthcare center in order to eliminate the underlying cause of her complaint of amorosis fugax, later applied to our hospital with the same complaint. At Doppler US performed in our hospital's radiology department, her right common carotid artery (CCA) was normal, but her left CCA was hypoplastic. The right internal artery (ICA) was validated as normal. At the left side, however, the ICA was apparent only as a stump and it did not demonstrate a continuity. The diagnosis of ICA agenesis was confirmed by the utilization of Doppler US, CT, and DSA imaging, and it was concluded also that ipsilateral CCA hypoplasia could be evaluated as an important clue to the diagnosis of ICA agenesis.